Feeding ecology of the subantarctic sea star Anasterias minuta within tide pools in Patagonia, Argentina - Gil, D. G. (2008)
The feeding ecology of the brooding sea star Anasterias minuta within tide pools was examined in Central and South Patagonia. 8 470 observations of sea stars were made. A. minuta does not feed while brooding. It consumes a wide range of prey, including molluscs and crustaceans, and can be regarded as a generalist or opportunistic predator. The purple mussel Perumytilus purpuratus was the most abundant prey item (57.6%). Other important prey were the gastropod Pareuthria plumbea, the isopod Exosphaeroma lanceolatum and the mussels Aulacomya atra atra and Mytilus edulis platensis. The proportion of sea stars feeding on sessile prey increases with sea-star size. A significant positive correlation was found between the size of the sea star and the size of the most frequent prey. The diet was fairly constant throughout the year, but diet composition differed between sites, shore level and sea-star size. The diversity of prey consumed by A. minuta was highest on the semi-exposed coast of Caleta Cordova Norte during the temperate season on the infralittoral fringe. A. minuta does not eat prey in proportion to its abundance beneath rocks within tide pools at the infralittoral fringe. Generally, the sea star consumed P. purpuratus and the gastropod P. plumbea more than other prey, even when they were not the most abundant prey present. At the midlittoral zone of the semi-exposed coast of Caleta Cordova Norte, the sea star feeds on prey species accordingly to their abundance. Larger P. purpuratus and E. lanceolatum were eaten disproportionately more often. A. minuta may have an opportunistic feeding strategy, taking unattached, wave-washed mussels when available rather that attached mussels. Consequently, it may have a variable impact on the community structure. Rev. Biol. Trop. 56 (Suppl. 3): 311-328. Epub 2009 January 05.